Residential location, commute distance, and body size: Cross-sectional observational study of state and territory capital cities in Australia. (September 2021) - Carroll, Suzanne J.; Turrell, Gavin; Dale, Michael J.; Daniel, Mark
Abstract: Introduction: Body size, a key risk factor for chronic diseases, is associated with longer commutes. This study assessed associations between residential proximity to capital city central business district (CBD), area-level commute distance, and individual-level body size (body mass index [BMI] and waist circumference [WC]), and whether commute distance partially explains associations between residential proximity and body size. Methods: This study used 2017-18 National Health Survey (NHS) data for working adults (aged ≥15 years, n = 6394) residing in Australian capital cities. Measures included individual-level sociodemographic information and measured body size (BMI, WC), area-level (SA1) disadvantage, average commute distance, and population density. SA1-centroid distances to CBDs were calculated and grouped into tertiles. Multilevel linear regression models estimated city-specific associations between commute distance and body size, and residential proximity and body size, accounting for area clustering and sequentially adjusting for covariates. Results: Commute distance was positively associated with BMI except in Adelaide and Darwin, and with WC in all cities except Darwin. Associations were largely unaffected by covariate adjustment in Sydney (β = 0.039, 95%CI: 0.004, 0.074) and Melbourne (β = 0.083, 95%CI: 0.045, 0.121) for BMI; and in Melbourne (β = 0.169, 95%CI: 0.074, 0.265) and Perth (β = 0.082, 95%CI: <0.001, 0.166) for WC. For other cities, associations were nullified. Distance to CBD was positively associated with BMI and WC in most cities, but robust to covariate adjustment (including commute distance) only in Darwin (BMI: middle tertile β = 1.60, 95%CI: 0.39, 2.81; WC: middle tertile β = 4.10, 95% CI: 0.45, 7.75) and Adelaide (WC: outer tertile β = 7.67, 95%CI: 2.65, 121.69). Conclusion: Living in middle and outer areas of Australia's capital cities is associated with greater body size. Longer commute distance partially accounts for this association in some cities. Integrated multisector planning may help to reduce the association between residential distance to CBD and commute distance on body size and thus health. Highlights: Unique join of residential distance-to-CBD data to Australian 2017-18 NHS data. Distance-to-CDB was associated with longer commute and greater body size. Longer commute distance was also associated with greater body size. Commute distance contributed to associations between distance to CBD and body size. Integrated multisector planning is needed to support health.